Pengaruh Penggunaan Media Pembelajaran Berbasis Augmented Reality terhadap Motivasi Belajar Siswa - Annisa Auliani Nursyafitri; Isrok’atun Isrok’atun; Nurdinah Hanifah (Syntax Corporation Indonesia, 2024)
In 21st century learning, teachers should be able to adjust to current conditions where technological developments can be utilized in the learning process. Learning media that utilizes technological developments in the field of education is Augmented Reality-based learning media. Augmented Reality as a learning media is expected to increase student learning motivation.The purpose of this study was to determine the effect of the use of Augmented Reality-based learning media on the learning motivation of grade VI elementary school students in learning social studies. This research uses a quantitative approach, Quasi Experimental Design with a Nonequivalent Control Group Design. The subjects of this research were class VI students at SDN 102 Cikudayasa with a total of 50 students divided into experimental class and control class. The data collection techniques used were tests, questionnaires, and interviews. Based on the results of data analysis shows that student learning motivation in learning social studies in experimental class which used Augmented Reality-based learning media has increased very well compared to the control class. So it can be concluded that there is an effect of Augmented Reality-based learning media on student learning motivation.